SISTEM BAGI HASIL USAHA PURSE SEINE DI KECAMATAN TEHORU KABUPATEN MALUKU TENGAH - Deby M Kewilaa (Indonesian Journal of Thousand Literacies, 2023)
The profit-sharing system that has occurred so far has always been fixed and tends to be very small compared to the income of the fishermen. The owner or employer makes profit-sharing provisions that will be offered attractively to the crew to be willing to work on their ship. Without thinking, ABK usually immediately accepts the offer of a jury to fish according to applicable regulations. The purpose of this study was to determine the Purse Seine Business Profit Sharing System in Tehoru District, Central Maluku Regency. Sampling is carried out by random technique (Proportionate Stratified Random Sampling), which is proportional sampling of random population members. The population in this study is a purse seine business unit in Tehoru District, Central Maluku Regency with a total of 9 fishing units. Quantitative data analysis is used to calculate income and revenue sharing obtained by fishermen. The results showed that when related to the needs of decent living (KHL) for Maluku Province at the time of the study, which was an average of Rp 306,288, - it means that the average income of fishermen obtained from purse seine fisheries is still below the specified decent needs. Thus, economically, the level of life of fishermen in Tehoru District can be said to be not at a prosperous level